Facilitators and barriers to participation and scale-up of a non-specialist delivered psychological intervention for adolescents in low-resourced settings: a process evaluation - Alissa M. Terp; Rand Habashneh; Felicity L. Brown; Adnan Abualhaija; Ibrahim S. Aqel; Maha Ghatasheh; Richard Bryant; Mark J. D. Jordans; Aiysha Malik; Ellenor Mittendorfer-Rutz; Aemal Akhtar (BMC Public Health)
Abstract Globally, the number of refugees and displaced individuals has surpassed 100 million for the first time in history. Refugees are more likely than non-refugee populations to experience psychological distress and develop mental disorders. Early Adolescent Skills for Emotion (EASE), developed by the World Health Organization, is a potentially scalable task-sharing intervention targeting symptoms of internalizing disorders such as depression and anxiety for 10–15 years old and their caregiver. Prior to this study a randomized controlled trial in Amman, Jordan was conducted showing effectiveness of EASE reducing caregiver distress and inconsistent disciplinary parenting as well as reducing internalizing problems in adolescence. This study aims to explore individual and contextual barriers and facilitators for scaling the EASE intervention for Syrian refugees in Jordan. Ten semi-structured interviews and four focus group discussions were conducted between October 2020 and February 2023 with five key mental health and psychosocial support (MHPSS) informants, eight EASE providers, 11 adolescents, and 12 caregivers. Purposeful quota sampling technique was used to recruit participants with attention to sex and age and number of interviews and focus group discussions determined through empirical saturation. Inductive and deductive codes were utilized in a six-step thematic analysis. Participants reported a beneficial impact of EASE sessions in terms of reducing experienced anxiety levels, improved communication between adolescents and caregivers, reduced feelings of anger and jealousy, and improved familial relationships. Individual participation was hampered by transportation issues, scheduling conflicts, gender-mixed groups, and competing responsibilities. Scale-up facilitators included; increased mental health awareness, perceived low cost of EASE, feasibility of delivery by non-specialists, and an intervention engaging both adolescents and caregivers. Barriers included location, online sessions, sustainability, general implementation issues caused by individual barriers, and some concerns about non-specialists. Results add nuances not detected in the previous randomized control trial in Jordan and provide important context for understanding effectiveness results. Future research should investigate the cost-effectiveness of EASE along with stepped-care implementation models to provide EASE within existing health systems.